2010
DOI: 10.1080/14786431003662572
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of intermittent flow and strain burst scaling behavior in LiF crystals during microcompression testing

Abstract: The first experimental statistical study is reported of intermittent plastic deformation of LiF microscopic samples having low initial dislocation densities, in both as-grown and gamma-irradiated conditions. The investigations used the microcompression testing method. Data sets were evaluated independently for the loading and flow deformation stages for each material. Investigations selectively examined evolution of the strainburst response in both the spatial and temporal domains. A revised analysis technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 42 publications
5
37
1
Order By: Relevance
“…Our results contrast with previous studies that have shown strong size effects in the plastic deformation of fee metals (Uchic et al, 2004;Greer et al, 2005;Volkert and Lilleodden, 2006) and ionic compounds (Nadgorny et al, 2008;Dimiduk et al, 2010). In particular, Nadgorny et al (2008) reported a strong size effect in [100] oriented LiF micropiUars fabricated by FIB when the micropillar diameter was in the range 1-10 urn.…”
Section: Effect Of Micropillar Size and Ion Irradiationcontrasting
confidence: 56%
See 1 more Smart Citation
“…Our results contrast with previous studies that have shown strong size effects in the plastic deformation of fee metals (Uchic et al, 2004;Greer et al, 2005;Volkert and Lilleodden, 2006) and ionic compounds (Nadgorny et al, 2008;Dimiduk et al, 2010). In particular, Nadgorny et al (2008) reported a strong size effect in [100] oriented LiF micropiUars fabricated by FIB when the micropillar diameter was in the range 1-10 urn.…”
Section: Effect Of Micropillar Size and Ion Irradiationcontrasting
confidence: 56%
“…Two sets of slip systems, {110}{110) and {100}{110), which are known to be responsible for the plastic deformation in LiF were included in the crystal plasticity model (Dimiduk et al, 2010;Gilman, 1959). …”
Section: Crystal Plasticity Modelmentioning
confidence: 99%
“…Such experiments measure the acoustic energy released by intermittent dislocation activity during constant stress deformation (in the tertiary creep regime). Indeed, via single sensor acoustic emission signals, such dislocation activity can be well characterised in time revealing power-law behaviour with exponents of 1.6 to 1.8, which is very similar to that seen via the micro-compression stress-strain curves 6,7,11 . Furthermore, via multiple sensor monitoring, time and space clustering of dislocation avalanches could be observed 19 .…”
Section: Introductionmentioning
confidence: 67%
“…As a result, the strain associated with the discrete dislocation activity is increased to an easily detectable magnitude. Whilst this more contemporary work has been primarily motivated by the "smaller-is-stronger" size-effect paradigm 4,5,[8][9][10] , an extensive analysis of the statistics of the discrete dislocation activity has revealed power-law behavior in the distribution of strainburst magnitudes giving an exponent of ≈ 1.6 − 2.2 6,7,11 . Similar exponents can also be found in bulk samples via detailed analysis of load displacement signals, where structural evolution is also seen to occur 12,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation